Indole-Terpenoids With Anti-inflammatory Activities From Penicillium sp. HFF16 Associated With the Rhizosphere Soil of Cynanchum bungei Decne - Pan, Guojun; Zhao, Yanfen; Ren, Shuang; Liu, Fengyang; Xu, Qicai; Pan, Weibin; Yang, Tongtao; Yang, Mingtian; Zhang, Xinru; Peng, Chuanyue; Hao, Gangping; Kong, Fandong; et al. (Frontiers in Microbiology, 2021)
Four new indole-terpenoids (1-4) named encindolene A, 18-O-methyl-encindolene A, encindolene B, and encindolene C, as well as three known analogues (5-7), were isolated from the fungus Penicillium sp. HFF16 from the rhizosphere soil of Cynanchum bungei Decne. The structures of compounds including absolute configurations were elucidated by spectroscopic data and ECD analysis. Anti-inflammatory activity evaluation revealed that compounds 1-7 inhibit the production of nitric oxide (NO) with IC50 values of 79.4, 49.7, 81.3, 40.2, 86.7, 90.1, and 54.4 μM, respectively, and decrease the levels of TNF-α, IL-6 contents in LPS-induced RAW 264.7 macrophages challenged by lipopolysaccharide (LPS).